Revision of the Palearctic Cicindela campestris species complex—Part 1: On the taxonomy, identification and ecology of Cicindela herbacea Klug, 1832 and Cicindela javetii Chaudoir, 1861 (Coleoptera, Cicindelidae) - Gebert, Jörg; Matalin, Andrey V.; Boetzl, Fabian A. (Zootaxa, 2021)
We revise the taxonomically problematic Palearctic Cicindela campestris species complex, a group of green tiger beetle species, using an integrative approach combining morphology, morphometry and biogeography. In this first part, an identification key to all subgroups of these green tiger beetles (Cicindela herbacea-subgroup, Cicindela javetii-subgroup, Cicindela desertorum-subgroup, Cicindela campestris-subgroup, Cicindela turkestanica-subgroup and Cicindela asiatica-subgroup) based on large series taken from private and museum collections as well as on literature sources is provided and diagnostic characters are illustrated by detailed photographs. The Cicindela herbacea- and Cicindela javetii-subgroups are revised and illustrated and identification keys as well as distribution maps for both are given. Four new synonyms are established: Cicindela herbacea herbacea Klug, 1832 = Cicindela herbacea aleppensis Deuve, 2012, syn. n.; Cicindela herbacea turkestanicoides W. Horn, 1938 = Cicindela herbacea perreaui Deuve, 1987, syn. n. = Cicindela herbacea colasi Deuve, 2011, syn. n.; Cicindela javetii javetii Chaudoir, 1861 = Cicindela thughurica Franzen, 2007, syn. n.